INTERNAÇÃO COMPULSÓRIA E O DIREITO HUMANO À SAÚDE: fraternidade e os paradoxos de internar para proteger em Mato Grosso do Sul - BRUCE HENRIQUE DOS SANTOS SILVA (2022)
In the present work, we study compulsory hospitalization and its connection with the human right to health, based on the meta-theory of fraternal law. Thinking about the role of the system of law and justice in protecting the human rights of people with mental disorders related to dependence on prohibited drugs, we seek to unveil the paradox of interning to protect. Critically, we propose a debate on the discourses of social control and their stigmas regarding the dependent, looking at the Judiciary, especially in Mato Grosso do Sul, to understand the consequences of a jurisdiction that is not attentive to fraternity and its role as guarantee fundamental rights. In addition to the bibliographic review to promote dialogue between the theoretical frameworks, we analyze the judicial processes that deal with compulsory hospitalization, in a descriptive examination, which leads to our conclusions. From vectors of gender, class and territory, investigating the medical and health discourses that underlie hospitalizations and the judges' reasons for deciding, we seek to answer the research problem: how the law and its practice have treated the compulsory hospitalization of dependents chemists of banned drugs in Mato Grosso do Sul, reaching the conclusion of the need to implement public policies in mental health as a path to fraternal law, beyond the judicial process.